Tindakan Preventif Guru Pendidikan Agama Islam Terhadap Eksistensi Paham Radikal Di Sekolah - Hirdha Nurfarini. Z.R; Fitriyah Fitriyah; Mardiana Mardiana; Muhammad Khairul Rijal (Institut Agama Islam Negeri (IAIN) Samarinda, 2018)
The development of the era goes hand in hand with human thought which is capable of touching various aspects of life, including religion. Many groups of people who are too excessive in studying religion in a way that is not right that ultimately results in the emergence of deviations of thought that deviates from the true nature which later became known as radical. Bearers of this radical understanding are also trying to spread their doctrine to various groups including the dominant schoolchildren who have a high level of curiosity. The purpose of writing this article is to provide education to several parties especially Islamic Religious Education teachers to address the spread of radical understanding in the school environment. The method that author use in this article is library research by gathering various library information. This article describes various efforts to promote radical understanding in spreading its doctrine and preventive actions that can be implemented by Islamic Religious Education teachers in schools.